2022
DOI: 10.3389/fonc.2021.717984
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lung Tumor Target Volume in a Large Sample: Target and Clinical Factors Influencing the Volume Derived From Four-Dimensional CT and Cone Beam CT

Abstract: Background and PurposeThis study aimed to systematically evaluate the influence of target-related and clinical factors on volume differences and the similarity of targets derived from four-dimensional computed tomography (4DCT) and cone beam computed tomography (CBCT) images in lung stereotactic body radiation therapy (SBRT).Materials and Methods4DCT and CBCT image data of 210 tumors from 195 patients were analyzed. The internal gross target volume (IGTV) derived from the maximum intensity projection (MIP) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…In this study, the displacements of SPTs measured using prospective and retrospective gating methods were compared, and the results were consistent with those of previous studies 8,18 . Li et al 9 . showed that the displacement amplitudes of lung tumors in the left–right, anterior–posterior, and superior–inferior directions were 1.6 mm, 2.2 mm, and 5.5 mm, respectively, which were within the range of displacement amplitudes observed in this study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the displacements of SPTs measured using prospective and retrospective gating methods were compared, and the results were consistent with those of previous studies 8,18 . Li et al 9 . showed that the displacement amplitudes of lung tumors in the left–right, anterior–posterior, and superior–inferior directions were 1.6 mm, 2.2 mm, and 5.5 mm, respectively, which were within the range of displacement amplitudes observed in this study.…”
Section: Discussionsupporting
confidence: 90%
“…4,5 This individual variability makes it challenging for radiation oncologists to accurately expand the safety margin and delineate the PTV based on traditional experience and documentation if they aim to cover the full range of tumor movement during the respiratory cycle. 6,7 Several researchers, including David, 8 Li, 9 and Guckenberger, 10 have used different methods to measure tumor displacement caused by respiratory motion. The use of fourdimensional (4D) cone beam CT (CBCT) technology allows the real-time observation of tumor trajectory and displacement measurement in three dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…Many methods have been used to study the quantitative effects of tumor movement on the target area, while there is no standard method until now ( 12 , 13 ). Target and clinical factors influencing the volume and dose derived from 4DCT and Cone beam CT was evaluation of lung cancer ( 14 ). Many researchers have been trying to find better methods to study the influencing of tumor motion by all kind of simulations ( 15 , 16 ).…”
Section: Introductionmentioning
confidence: 99%